Marriott international inc. equity research - the hotel Giant´s recovery - Neves, Daniel Duarte (2022)
This report, which is part of a broader Equity research on Marriott International Inc., aims to establish a price target for the analysed company. At a time where financial markets are faced with tremendous uncertainty, depicting the intrinsic value of Marriott based on its underlying value drivers becomes ever more relevant. Departing from the projections on how the US-based hotel chain will evolve in the future, both absolute and relative valuation methods will be used to establish a price target of $173,12 for December 2022. Resulting in an estimated shareholder return of 11,66% a BUY recommendation will be provided to prospective investors.